Android-Based Halal Product Educational Game To Improve Student Skills In Learning Islamic Religious Education At School - Lucky Enggrani Fitri; Dedy Setiawan; Hayati, Suci (International Journal of Technology and Education Research, 2024)
Educational games are fun activities that contain educational content, which is considered very important. Knowing halal food is very important for a Muslim, so this should be introduced early, especially in elementary school. The aim is to form children's personalities who always prioritize halal things and are familiar with various halal products. This research aims to design and build an educational game application about halal products for young children, which will be run on the Android platform. The test results show: 1) Application functionality, tested using black-box testing, provides valid results. 2) Performance efficiency shows no memory leaks and CPU usage is stable between 7% - 17% after 9 seconds of use. 3) Application compatibility runs well on Android 7.0 Nougat to Android 10 devices